Three-Dimensional kinetic adaptations of gait throughout pregnancy and postpartum - Branco, Marco A. C. (2016)
The present publication was supported by the following projects: (1) funder, Fundação para a Ciência e Tecnologia (FCT)/Portuguese Foundation for Science and Technology, project title: Effect of Biomechanical Loading on the Musculoskeletal System in Women during Pregnancy and the Postpartum Period; promoter, CIPER/FMH-UL/ESDRM-IPS; Principal Researcher, Rita Santos-Rocha; and project reference, PTDC/DES/102058/2008; (2) funder, European Union: QREN-InAlentejo-Programa Operacional do Alentejo-2007–2013/National Strategic Reference Framework, project title: Alentejo’s Science and Technology Park, Sport and Health Research Center; promoter: Polytechnic Institute of Santarém, Sport Sciences School of Rio Maior/Health School of Santarém; Project Coordinator, Rita Santos-Rocha; and project reference, ALENT-07-0262-FEDER-001883.